Zeolite Application in Wastewater Treatment - Luciano Fernandes de Magalhães; Gilberto Rodrigues da Silva; Antônio Eduardo Clark Peres (Adsorption Science & Technology)
As a scarce natural resource, the preservation of water quality is of fundamental importance to guarantee its availability for future generations. Due to the increasing industrial activity, effluents are generated with a series of chemical compounds, such as nitrogenous, phosphoric, and organic compounds, heavy metals, and dyes which, if improperly disposed of, contribute to contamination, followed by significant environmental impacts, in addition to the damage to human health. The adsorption technique is an effective approach for removing contaminants from effluents, showing high versatility, due to the use of various materials as adsorbents. Belonging to a wide variety of materials, zeolites reveal to be a promising adsorbent. Zeolites are minerals found in nature or which can be synthesized from industrial residues, standing out in the treatment of contaminated effluents. Zeolite removal efficiency depends on the contaminant to be removed and can reach up to 96% for heavy metals, 90% for phosphoric compounds, 96% for dyes, 80% for nitrogen compounds, and 89% for organics. Aiming at the identification of the more relevant findings and research gaps to advance the use of zeolites in the large-scale treatment of industrial effluents, a review on the recent application of zeolites is needed. This paper presents a global view of zeolites, and a review is conducted on several recent studies using zeolites as adsorbents for the contaminants considered, indicating the main characteristics of the various adsorption systems, demonstrating the particularities of each process, and aiming to reveal useful information to provide future research, in addition to identifying points that need further investigation.